Prevalence of Suicidal Ideation and Planning in Senior Medical Students - Osama Habib, Muhammad Atif Qureshi, Khalid Mahmood, Munaza Javed, Nasir Iqbal, Aniqa Anser, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Medical students have considerably higher prevalence rates of depression and suicidal thoughts as compared to their age-fellows from the general population. Only a limited number of studies have previously investigated the suicidal thinking/planning in Pakistani medical students. The aim of this study was to assess the prevalence rates of suicidal thoughts and planning in medical students studying at a private medical college in Lahore, Pakistan. Place and duration: Fourth year and final year medical students at Azra Naheed Medical College, Lahore were invited to voluntarily take part in this study. The study was conducted from 15th of June to the 15th of July 2022. Study design: Cross-sectional descriptive study Methodology: Suicide behavior questionnaire revised (SBQ-R) was used as the study instrument. Data collection was anonymous and the study was approved by the local institutional review board. The study was approved by the Institutional review board of Azra Naheed Medical College, Lahore. Descriptive statitstics were employed to report the findings and SPSS version 26 was used to store and analyze the data. Results: A total of 248 medical students (51.5% female) participated in the study. The prevalence of suicidal thoughts/plans in the past was 36.3% and the prevalence of suicidal thoughts in the past year was 31%. More than 16% of students communicated their intent to commit suicide to someone else in the past and 7% of the students reported that it was likely, rather likely or very likely that they will attempt suicide in the future. Conclusions: The prevalence of suicidal thoughts/ planning in medical students is worryingly high. Medical teachers should routinely assess their students for the presence of depressive symptoms/suicidal thoughts and offer support for students who screen positive for these. Key words: Suicide, Medical students, Prevalence